Distributional Effects of Adopting Carbon Tax in India: An Economic Analysis. (December 2013) - Rathore, Pooja; Bansal, Sangeeta
In international forums discussing ways to address climate change, carbon tax has been proposed as a policy instrument to mitigate greenhouse gas emissions. The cost of implementation of the policy, however, may be distributed differently across different sections of the society. Existing studies from developed and developing countries found mixed results of distributional effects of a carbon tax, and the effect of carbon tax on a developing country like India is still unclear. This study examines the distributional effects of adopting carbon tax in India. It uses the 2009–10 national sample survey data covering over 100855 households and analyses the rural and urban areas separately. A budget share approach with a summary measure of Suit Index has been applied to examine the direct effect of carbon tax on Indian households. We find that carbon tax in India is mildly progressive and this progressivity is higher in rural sector as compared to urban sector. The progressivity also varies between different fuels. In comparison to electricity and LPG, carbon tax is regressive for kerosene in India.